Definisi Hadits dan Unsur-Unsur Kritik Matan: Retrospektif dan Pendekatan Praktis - Herliawati, Lia; Yulistiani, Siti Alfiah; Humairo, Shovi Sholahiyah; Zikrullah, Muhammad; Makmudi (At-Tadris: Journal of Islamic Education, 2025)
This study discusses the definition of hadith and the importance of matn criticism in maintaining the quality of hadith. Etymologically, hadith has several meanings such as conversation, news, and something new. The terminology of hadith encompasses everything related to Prophet Muhammad SAW, including his words, actions, and attributes. The elements of hadith consist of sanad (chain of narration), matn (text of the hadith), and rawi (narrator of the hadith). Matn criticism means the analysis of the hadith content, aimed at ensuring the validity of hadith by considering the aspects of sanad and matn. Therefore, this activity is crucial to distinguish between sahih (authentic) and daif (weak) hadiths and avoid accepting incorrect narrations. The study also highlights that matn criticism is a positive effort to preserve the purity of hadith and deepen understanding of the teachings of Prophet Muhammad SAW.